Candida glabrata biofilms response to amphotericin B - Rodrigues, Célia Fortuna (2015)
Background: Candida species are responsible for recurrent human infections, mostly in immunocompromised patients, due to their high vulnerability. Candida glabrata has been showing to have a major role in these infections being the second most prevalent species involved in human fungemia. Amphotericin B (AmB), a common antifungal drug, is a hospital-environment exclusive polyene, normally being efficient when used to fight candidiasis. Objectives: The main goal of this work was to infer about the influence of AmB in Candida glabrata biofilms formation and its effect on matrix composition and ERG genes expression. Methods: Candida glabrata biofilms were formed in the presence of AmB and analyzed by dry weight. Moreover, ERG genes expression was evaluated by qRT-PCR and matrix was analyzed in terms of composition in carbohydrates, proteins, beta-glucans and a new finding: ergosterol. Conclusions: In addition to an inefficient reduction of the C. glabrata biofilms, this work showed that ERG genes seem to be less involved than the matrix composition in C. glabrata biofilms response to AmB. Specifically, C. glabrata biofilms matrices respond with an increase of carbohydrates, particularly beta-1,3 glucans, and with a decrease of total proteins. The ergosterol values did not expressively changed in the presence of AmB. The present work support the theory of multifaceted mechanisms developed by C. glabrata biofilms as response to the presence of AmB.